Can pay, should pay? Exploring employer and student perceptions of paid and unpaid placements. (July 2015) - Smith, Sally; Smith, Colin; Caddell, Martha
Students can benefit from applying their emerging skillsets through a work placement, both in terms of consolidating their learning and in gaining a better appreciation of their subject area. However, the main motivation for students in completing a work placement is in their increased employability skills. The aim of this study is to identify the core issues underpinning the 'paid versus unpaid' student work debate through a unique opportunity to access student and employer experiences. The study explores motivations, experiences and outcomes from different placement models – both paid and unpaid – for students and employers. Using separate surveys for students and employers, drivers, motivations and experiences were explored. Employers from large multi-nationals to small- and medium-sized enterprises, from profit-making organisations to the third sector, took part in the study. Overall, the data support the argument that placements should be paid, highlighting the benefits accruing both to students and to employers from payment being a component of the placement experience. This is particularly the case when a placement is for an extended period of time and the work being undertaken is equivalent to that of a regular employee. However, the value of work experience to students, paid or unpaid, emerges strongly from the study, and so, finally, the article highlights issues and questions arising for the higher education sector.